Respuesta :
Answer:
The answer to your question is below
Step-by-step explanation:
- The Standard form of the equation is
(x - h)² + (y - k)² = r²
4.
Center (8, -4) r = [tex]\sqrt{118}[/tex]
-Substitution
(x - 8)² + (y + 4)² =[tex]\sqrt{118}[/tex]²
-Result
(x - 8)² + (y + 4)² = 118
5.
Center (-10, 9) r = [tex]\sqrt{37}[/tex]
-Substitution
(x + 10)² + (y - 9)² = [tex]\sqrt{37}[/tex]²
-Result
(x + 10)² + (y - 9)² = 37
6.-
Center (-8, 0) r = 6
-Substitution
(x + 8)² + (y - 0)² = (6)²
-Result
(x + 8)² + (y - 0)² = 36
Answer:
4. (x - 8)² + (y + 4)² = 118
5. (x + 10)² + (y - 9)² = 37
6. (x + 8)² + y² = 36
Step-by-step explanation:
Equation of a circle:
(x - h)² + (y - k)² = r²
4. Center: (8, -4), Radius: sqrt{118}
(x - 8)² + (y - (-4))² = (sqrt(118))²
(x - 8)² + (y + 4)² = 118
5. Center: (-10, 9), Radius: sqrt{37}
(x - (-10))² + (y - 9)² = (sqrt(37))²
(x + 10)² + (y - 9)² = 37
6. Center: (-8, 0), Radius: 6
(x - (-8))² + (y - 0)² = 6²
(x + 8)² + y² = 36